Analisis Anteseden E-Money Adoption pada Masyarakat di Kota Batam - Wijaya, Della Jane; Firdiansyah, Ronny Arief; Peranginagin, Pulung (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim: This study intends to determine the intensity of people's behavior in using electronic money. Design/Approach: This study was designed with a survey research model. Research Finding: The study's outcome indicates that ease of use, performance risk expectations, habits, and COVID-19 risk had a significant positive effect on the actual use of e-money with behavioral intensity as mediation. Theoretical contribution/Originality: This research shows that the use of e-money increased during pandemics. Practitioner/Policy implication: This research can be useful for the e-money platform as material for R&D to provide expansion and improvement of the business side of the e-money company. Research limitation: This research solely centered on several variables, i.e. ease of use, performance risk expectations, habits, and Covid-19 risk.